Sintering of synthetic hydroxyapatite compacts - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
Hydroxyapatite (HA) is a particularly attractive material for bone and tooth implants because of its chemical and crystallographic properties, which closely resemble those of bone and tooth minerals. Moreover, sintered HA material has superior biocompatibility. In this study, the compacts made of pure HA (Merck) were sintered at 1000, 1100, 1200 and 1300degreesC. The density, microhardness and compression strength tests were performed, in order to find out the optimum sintering temperature. As a result, average density was 2.554 +/- 0.37 g/cm(3), average compression strength value was 25.22 +/- 12 MPa and average value of Vickers microhardness was found as 250 +/- 120 HV (kg/mm(2)).
Keywords: hydroxyapatite; sintering; compacts; mechanical properties; MECHANICAL-PROPERTIES; COMPOSITES; CERAMICS